2012
DOI: 10.1590/s0100-06832012000200034
|View full text |Cite
|
Sign up to set email alerts
|

Chemical properties of soils treated with biological sludge from gelatin industry

Abstract: summary the impact of agro-industrial organic wastes in the environment can be reduced when used in agriculture. from the standpoint of soil fertility, residue applications can increase the organic matter content and provide nutrients for plants. this study evaluated the effect of biological sludge from gelatin industry on the chemical properties of two ultisols (loamy sand and sandy clay) and an oxisol (clay). the experiment lasted 120 days and was carried out in laboratory in a completely randomized design w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 12 publications
(6 reference statements)
1
17
0
2
Order By: Relevance
“…Guimarães et al (2012) também não constataram alterações no teor de matéria orgânica do solo com a adição de até 500 m 3 ha -1 de resíduo orgânico (lodo biológico de indústria de gelatina).…”
Section: Resultsunclassified
“…Guimarães et al (2012) também não constataram alterações no teor de matéria orgânica do solo com a adição de até 500 m 3 ha -1 de resíduo orgânico (lodo biológico de indústria de gelatina).…”
Section: Resultsunclassified
“…The main consequences of increased organic matter content for soil fertility are increased nitrogen pools for plants and higher CEC (GUIMARÃES et al, 2012).…”
Section: A B C Dmentioning
confidence: 99%
“…To three soils with different clay contents and CEC potential, Guimarães et al (2012) applied up to 500 m 3 ha -1 biological sludge from the gelatine industry and found that the soils with lower buffering capacity responded with a higher pH increase to the organic residues.…”
Section: Bmentioning
confidence: 99%
“…A carência de informações científicas, embasadas em experimentação de campo de longa duração, induz à baixa eficiência de uso dos subprodutos gerados pelas agroindústrias, observando-se que o solo é utilizado mais como meio de descarte desses materiais do que para seu aproveitamento racional (LIMA et al, 2007;CHEPOTE, 2003;MANTOVANI et al, 2005;PRIMO et al, 2010;ARAÚJO et al, 2008;COSTA et al, 2009;GUIMARÃES et al, 2012;GIANELLO et al, 2011).…”
Section: Introductionunclassified